1995
DOI: 10.1029/95ja01161
|View full text |Cite
|
Sign up to set email alerts
|

Pitch angle scattering of diffuse auroral electrons by whistler mode waves

Abstract: Resonant electron-whistler interactions in the plasma sheet are investigated as possible explanations of the nearly isotropic fluxes of low-energy electrons observed above the diffuse aurora. Whistler mode waves, propagating near the resonance cone with frequencies near or larger than half the equatorial electron cyclotron frequency, can interact with low-energy plasma sheet electrons. A Hamiltonian formulation is developed for test particles interacting with the coherent chorus emission spectra. We consider t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…These are electron interaction with electromagnetic whistler mode waves (Kennel and Petscheck, 1966;Bespalov and Trakhtengerts, 1986;Johnstone et al, 1993;Villalón and Burke, 1995) and interaction with electrostatic electron cyclotron harmonic (ECH) waves (Kennel et al, 1970;Lyons, 1974;Horne and Thorne, 2000). While the interaction of whistler mode waves with high energy electrons (E>10 keV) was proved theoretically and experimentally, it was not clear that these waves would effectively interact with electrons at energies less than 10 keV that are typical of the diffuse auroral zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are electron interaction with electromagnetic whistler mode waves (Kennel and Petscheck, 1966;Bespalov and Trakhtengerts, 1986;Johnstone et al, 1993;Villalón and Burke, 1995) and interaction with electrostatic electron cyclotron harmonic (ECH) waves (Kennel et al, 1970;Lyons, 1974;Horne and Thorne, 2000). While the interaction of whistler mode waves with high energy electrons (E>10 keV) was proved theoretically and experimentally, it was not clear that these waves would effectively interact with electrons at energies less than 10 keV that are typical of the diffuse auroral zone.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main candidates. The first is that the particle precipitation is a result of pitch angle diffusion due to interaction of particles with electrostatic electron cyclotron harmonic (ECH) waves (Kennel and Petscheck, 1966;Bespalov and Trakhtengerts, 1986;Johnstone et al, 1993;Villalón and Burke, 1995). The alternative theory is electron scattering by whistler mode waves (Kennel et al, 1970;Lyons, 1974;Horne and Thorne, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, Inan et al [1992] reported, on the basis of modeling work, that upper band (UB) whistler mode waves could scatter electrons in a range of energies from 1 to 10 keV into the loss cone. In addition, Villalón and Burke [1995] suggested that plasma sheet electrons scattered into the loss cone by whistler mode waves would produce a diffuse aurora. Our data clearly show that electron flux with energies greater than 2 keV is deficient in regions corresponding to black auroras, while electron flux corresponding to the surrounding diffuse aurora with energies below 2 keV shows no change.…”
Section: Discussionmentioning
confidence: 99%
“…In the downward electron data, we identify two types of large-scale electron precipitations: one type includes plasma sheet electrons that precipitate continuously from the beginning to the end, mostly in the keVenergy range, except for some deficiencies or dropouts, and the other represents low-energy (∼100-2000 eV) inverted V electrons from 08:15:17 to 08:15:29 UT. The former plasma sheet electron precipitation is not shaped like an inverted V, indicating that it was probably precipitated by pitch angle scattering [e.g., Johnstone et al, 1993;Villalón and Burke, 1995]. It seems that the low-energy inverted V electrons rarely contribute to the E region auroral emissions measured by MAC, since the E region aurora is generally produced by keV-range electrons.…”
Section: Black Arc Eventmentioning
confidence: 99%
“…Resonant wave-particle interactions play an essential role in understanding the dynamics of radiation belt energetic electrons (e.g., Lyons et al, 1972;Summers et al, 1998Summers et al, , 2007aSummers et al, , 2009O'Brien et al, 2003;Albert, 2004Albert, , 2005Albert, , 2008Horne et al, 2005a, b;Meredith et al, 2003Meredith et al, , 2006Meredith et al, , 2007Meredith et al, , 2009aMiyoshi et al, 2006;Li et al, 2007;Shprits et al, 2008aShprits et al, , b, 2009bShprits et al, , 2011Thorne et al, , 2007Zong et al, 2009;Thorne, 2010;Xiao et al, 2009aXiao et al, , 2010b and plasma sheet source electrons (e.g., Inan et al, 1992;Johnstone et al, 1993;Villalón and Burke, 1995;Horne and Thorne, 2000;Horne et al, 2003;Ni et al, 2008Ni et al, , 2011aSu et al, 2009;Thorne et al, 2010;Tao et al, 2011b). To demonstrate the gyroresonant diffusion processes of magnetospheric electrons due to various plasma waves, quasi-linear theory has been well established assuming that the particle distribution function averaged over space changes slowly on time scales associated with the motion of the waves (Kennel and Engelmann, 1966).…”
Section: Introductionmentioning
confidence: 99%